Research on environmental justice in China : limitations and possibilities - Mah, Alice; Wang, Xinhong (Chinese Journal of Environmental Law, 2017)
This note focuses on current sociological research being conducted in China on the concept of environmental justice. It critically reviews how the concept has been used in the Chinese context since the 1990s, evaluating some of the possibilities and limitations of the concept. We argue that environmental justice is a useful concept in the context of China, due to its resonance with environmental concepts and axes of social mobilization (particularly in relation to procedural justice and law), its capacity to address social as well as environmental issues of structural inequality together, and its resonance with shared ideas of social justice within Chinese legal traditions. However, the concept of environmental justice also has clear limitations. Practically, environmental justice has been used predominantly in the academic sphere in China, with very little take-up in civil society discussions about the environment.